Complaint management and redress mechanism: the effect of fragmented institutional approach in regulating consumer credit in Malaysia - Hassan, Rusni; Ilias, Ibtisam @ Ilyana; Kassim, Salina; Hingun, Mohsin; Abu Bakar, Elistina (Islamic World Network for Environmental Science and Technology, 2018)
Complaint management and redress mechanism constitute cardinal elements of financial consumer protection which should be provided by the financial consumer protection regulator. This study explores the role of the Central Bank of Malaysia, the Ministry of Domestic Trade and Consumer Affairs as well as the Ministry of Housing and Local Government to ensure proper complaint management and redress mechanism in favour of financial consumers of different segments of consumer credit. Applying doctrinal, qualitative and comparative law research methodology, the study finds that as a result of fragmented approach in regulating consumer credit in Malaysia, these aspects are pursued with different priorities and enthusiasm by respective regulators. Thus, the benefit of protection varies from one class of financial consumers to another. To ensure consistency and efficient protection, the study proposes for the establishment of a single regulator, the approach adopted by Australia, a jurisdiction renowned with an established track record in financial consumer protection regime. It is viewed that by establishing a single regulator, a uniform platform for complaint and redress will be provided thereby ensuring equal protection to wide array of financial consumers.